1982
DOI: 10.1007/bf00710848
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of S-100 protein binding sites in synaptosomal fractions and subfractions

Abstract: 1. Immunocytochemical evidence is presented of the ultrastructural localization of binding sites for S-100 protein in synaptosomal fractions and subfractions. Synaptosomes or isolated synaptosomal subfractions were first incubated with S-100, then centrifuged to remove unbound S-100, and finally fixed before treatment with anti-S-100 antiserum, using the unlabeled antibody peroxidase-antiperoxidase (PAP) method. 2. When intact synaptosomes were used, the immunoreaction product was localized to the postsynaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…74,75 Additionally, two studies that investigated the localization of S100 proteins in synaptosomal fractions showed that divalent cations such as Ca 2+ and Mg 2+ were necessary for S100 proteins to interact directly with synaptosomes. 73,76 While these studies highlight the role of S100 proteins in the neuronal synaptosome, it is possible that the binding of Ca 2+ can affect the function and/ or secretion of S100 proteins from glial cells as well.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…74,75 Additionally, two studies that investigated the localization of S100 proteins in synaptosomal fractions showed that divalent cations such as Ca 2+ and Mg 2+ were necessary for S100 proteins to interact directly with synaptosomes. 73,76 While these studies highlight the role of S100 proteins in the neuronal synaptosome, it is possible that the binding of Ca 2+ can affect the function and/ or secretion of S100 proteins from glial cells as well.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In further studies, it would be interesting to explore whether changes in intracellular Ca 2+ levels result in specific conformational changes in S100A5 that promote secretion or conversely exert general effects on the secretion machinery. Several studies show that S100 calcium-binding proteins exposed to high intracellular Ca 2+ levels can bind Ca 2+ and subsequently adopt a conformation that exposes hydrophobic sites that then enables them to bind target proteins or membranes. , Interestingly, S100 proteins have also been reported to be associated with synaptosomes, including several recent proteomic studies that reveal the presence of S100 proteins in the synaptosome. Several other studies show that S100 proteins are able to form tight complexes with binding sites in synaptosomal particulate fractions in both time- and temperature-dependent manners and are shown to also localize to the synaptosome in mouse brain cortex. , Additionally, two studies that investigated the localization of S100 proteins in synaptosomal fractions showed that divalent cations such as Ca 2+ and Mg 2+ were necessary for S100 proteins to interact directly with synaptosomes. , While these studies highlight the role of S100 proteins in the neuronal synaptosome, it is possible that the binding of Ca 2+ can affect the function and/or secretion of S100 proteins from glial cells as well.…”
Section: Discussionmentioning
confidence: 99%